The naval war film : genre, history, national cinema - Rayner, Jonathan (Jonathan R.) (Manchester University Press, 2007)
Undertaking a coherent and comprehensive consideration of the depiction of naval warfare in the cinema, this book focuses on the examination of the films which seeks to determine whether the distinctive characteristics of naval film narratives justify their categorization as a separate genre or sub-genre in popular cinema.